Occupational Health and Safety Risk Analysis Using JSA and FMEA in Fatty Acid Tank Maintenance at PT Bramindra Indotama Gresik - Arif Afandi; Deny Andesta; Yanuar Pandu Negoro (TALENTA Publisher, 2026)
This study aims to identify potential occupational hazards and assess the level of occupational health and safety (OHS) risks in the maintenance activities of the fatty acid tank at PT Bramindra Indotama Gresik using an integrated Job Safety Analysis (JSA) and Failure Mode and Effects Analysis (FMEA) approach.This research employs a qualitative descriptive approach, with data collected through direct observation, interviews, and questionnaires administered to maintenance workers and Health, Safety, and Environment (HSE) personnel. JSA was used to identify work steps and potential hazards, while FMEA was applied to evaluate risk levels based on Severity, Occurrence, and Detection, resulting in a Risk Priority Number (RPN). The results indicate that several activities fall into high-risk categories, particularly during Lock Out Tag Out (LOTO), tank cleaning and draining, and inspection of components inside the tank. The highest RPN values were associated with hazards related to residual energy, confined space conditions, and manual handling. The implementation of risk control measures based on the hierarchy of controls is expected to reduce workplace accident risks, improve compliance with safety procedures, and strengthen the OHS culture. Therefore, the integration of JSA and FMEA is proven to be an effective approach for identifying hazards and prioritizing risk control in maintenance activities.